Authentic cultural communication: A collaborative Intercampus Cultural Awareness Project - Sánchez Víquez, Andrea (2021)
This investigation acknowledges and explores the cultural differences within the Costa Rican society by performing a cultural awareness project with university students from the same course but in different regions of the country.  It will outline from both the professors and the students’ perspectives how the project was successful and effectively met the course objectives. Through a quantitative analysis, this article claims that inter-campus projects present an authentic opportunity for successful intercultural communication and also significant opportunities for collaborative teaching.